Acoustic radiation force impulse (ARFI) elastography to asses maternal and foetal structures in pregnant ewes - Silva, Priscila D. A. da [UNESP]; Uscategui, Ricardo Andres R. [UNESP]; Santos, Victor J. C. [UNESP]; Taira, Augusto R. [UNESP]; Mariano, Renata S. G. [UNESP]; Rodrigues, Mariana G. K. [UNESP]; Simoes, Ana Paula R. [UNESP]; Maronezi, Marjury C. [UNESP]; Avante, Michelle L. [UNESP]; Monteiro, Frederico O. B.; Vicente, Wilter R. R. [UNESP]; Feliciano, Marcus A. R. [UNESP] (Wiley-Blackwell, 2019)
Contents The aim of this study was to evaluate the stiffness of foetal lungs, liver, kidneys and placentomes by acoustic radiation force impulse (ARFI) elastography in ovine and to correlate obtained findings with foetal development. Twenty-four ewes were included, and tissue stiffness of foetal lung, liver, kidney and placentome was measured beginning with 10th gestational week by qualitative-quantitative ARFI elastography. A total of 33 healthy lambs were born. Qualitative elastographic analysis permitted to classify maternal and foetal tissues elasticity in decreasing order as follows: placentome, kidney, liver and lung. Regarding quantitative ARFI elastography data, shear wave velocity (SWV) of foetal lung and liver varied. The lung SWV decreased gradually from the 16th to the 21st gestational week (R-2 = 0.80; p < 0.001), while liver SWV increased gradually from the 14th to 21st gestational week (R-2 = 0.80; p < 0.001). In contrast, the kidneys and placentomes SWV's remained constant through gestation (p = 0.076; and 0.34). ARFI elastography was shown feasible for evaluation of maternal and foetal tissues stiffness in the ovine model. It can be used to demonstrate pulmonary and hepatic stiffness modifications during foetal development.
Keywords: elastography; foetal development; ovine; pregnancy; ultrasonography